Oscillatory changes in cognitive networks activated during a three-stimulus visual paradigm: an intracerebral study - Bočková, M; Chládek, J; Šímová, L; Jurák, P; Halámek, J; Rektor, I (Clinical neurophysiology, 2013)
OBJECTIVE: The aim of this work was to study the oscillatory changes during target and distractor stimuli processing. We focused mainly on responses after distractor stimuli in the prefrontal cortex and their possible relation to our previous results from the basal ganglia. METHODS: Five epilepsy surgery candidates with implanted depth electrodes performed a three-stimulus paradigm. The frequent stimulus (70%; without required response) was a small blue circle, the target stimulus (15%; with motor response) was a larger blue circle, and the distractor stimulus (15%; without required response) was a checkerboard. The SEEG signals from 404 electrode contacts were analysed using event-related de/synchronization (ERD/S) methodology. RESULTS: The main response to the target stimuli was ERD in the alpha and low beta bands, predominantly in the motor control areas, parietal cortex and hippocampus. The distractor stimuli were generally accompanied by an early theta frequency band power increase most markedly in the prefrontal cortex. CONCLUSIONS: Different ERD/S patterns underline attentional shifting to rare target ("go") and distractor ("no-go") stimuli. SIGNIFICANCE: As an increase in lower frequency band power is considered to be a correlate of active inhibition, the prefrontal structures seem to be essential for inhibition of non-required movements.
Keywords: Epilepsy; Prefrontal Cortex; Models, Neurological; epilepsie; Humans; prefrontální mozková kůra; beta rytmus EEG; evokované potenciály; modely neurologické; kognice; Alpha Rhythm; Female; dospělí; korová synchronizace; alfa rytmus EEG; lidé; elektroencefalografie; Photic Stimulation; světelná stimulace; Cortical Synchronization; Adult; ženské pohlaví; Male; Evoked Potentials; Adolescent; Beta Rhythm; Psychomotor Performance; Electroencephalography; biologické hodiny; mužské pohlaví; Cognition; Biological Clocks; psychomotorický výkon; mladiství